Visitors' awareness on the conservation of Putrajaya Wetland Park - Mohd Kasim, Mohamad Kharsidi (2016)
Realising the positive impacts of preserving and conserving the natural environment on peoples’ quality of life certain areas have been developed as preservation and conservation sites of the natural environment in an effort to enhance the biodiversity and ecological integrity of local flora and fauna. However, such activities did not normally attract much attention, cooperation and commitment of both the general public and the private sector as they did not bring in direct and substantial material benefits and profits. This study gauged visitors awareness of the preservation and conservation of Putrajaya Wetland Park, the first and largest man-made lakes in Malaysia and examine the types of visitors who visited the Putrajaya Wetland Park. This study used quantitative methods through 200 questionnaires. Overall, the study found that there were still many who did not know about the exact ecological functions of the Putrajaya Wetland Park. The demographic background of the respondents such as gender, age, race, education level, and occupation was obtained. Most of the visitors were married (66%) and also most of them were degree holder (48%). Data obtained were analyzed with a ‘Multiple Linear Regression' in Statistical Package for Social Science (SPSS). In this study, it is hoped that it can give some indication of visitor awareness of conservation in the Putrajaya Wetland Park.